2014
DOI: 10.1021/ac5039303
|View full text |Cite
|
Sign up to set email alerts
|

Fully Automated Sample Preparation Microsystem for Genetic Testing of Hereditary Hearing Loss Using Two-Color Multiplex Allele-Specific PCR

Abstract: A fully automated microsystem consisting of a disposable DNA extraction and PCR microchip, as well as a compact control instrument, has been successfully developed for genetic testing of hereditary hearing loss from human whole blood. DNA extraction and PCR were integrated into a single 15-μL reaction chamber, where a piece of filter paper was embedded for capturing genomic DNA, followed by in-situ PCR amplification without elution. Diaphragm microvalves actuated by external solenoids together with a "one-way"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 27 publications
0
20
0
1
Order By: Relevance
“…Compared to other alternative methods, 4,7,8 the proposed microdevice has the following four advantages: (1) because this microfluidic chip does not contain any extra components such as microelectrodes or piezo transducers, the fabrication process is simple and the cost is low; (2) the device eliminates the need for complicated external instruments, aside from two pumps for fluid control, making the device easy to automate and miniaturize; (3) the chip material (PDMS) can be replaced with polymethyl methacrylate or other polymer materials that are easy for mass production, 28 and thus the microfluidic chip has a great potential to be transformed into a disposable product for forensic analysis of sexual assault cases; and (4) the microdevice is easily integrated, and the integration of this microfluidic chip with subsequent sample processing chips (e.g., DNA extraction, PCR, or STR chips 29,30 ) may offer a chance to replace the conventional labor-consuming and time-consuming processes for forensic evidence analysis.…”
Section: Separation Performance Analysismentioning
confidence: 99%
“…Compared to other alternative methods, 4,7,8 the proposed microdevice has the following four advantages: (1) because this microfluidic chip does not contain any extra components such as microelectrodes or piezo transducers, the fabrication process is simple and the cost is low; (2) the device eliminates the need for complicated external instruments, aside from two pumps for fluid control, making the device easy to automate and miniaturize; (3) the chip material (PDMS) can be replaced with polymethyl methacrylate or other polymer materials that are easy for mass production, 28 and thus the microfluidic chip has a great potential to be transformed into a disposable product for forensic analysis of sexual assault cases; and (4) the microdevice is easily integrated, and the integration of this microfluidic chip with subsequent sample processing chips (e.g., DNA extraction, PCR, or STR chips 29,30 ) may offer a chance to replace the conventional labor-consuming and time-consuming processes for forensic evidence analysis.…”
Section: Separation Performance Analysismentioning
confidence: 99%
“…More complex cell concentration methods involve manipulating the flow of cells using size or charge based differentiation methods (Pratt et al 2011 ). Simpler cell capture approaches using a physical substrate, such as a filter, (Baier et al 2009 ; Gulliksen et al 2012 ; Gan et al 2014 ; Zhuang et al 2015a , b ) or beads (Cho et al 2007 ; Ritzi-Lehnert et al 2011 ) have also been demonstrated on microfluidic platforms. However, these methods require electrical power to control the sample flow or the magnetic beads.…”
Section: Introductionmentioning
confidence: 99%
“…A μCE system capable of multi‐channel confocal laser‐induced fluorescence detection was built in‐house and has been previously described in detail by Zhuangbin et al . Briefly, the microchip was coated with surface coating agent and loaded with polymer solution by pipetting DNA samples into the sample well.…”
Section: Methodsmentioning
confidence: 99%
“…A lCE system capable of multi-channel confocal laserinduced fluorescence detection was built in-house and has been previously described in detail by Zhuangbin et al (19) the microchip was coated with surface coating agent and loaded with polymer solution by pipetting DNA samples into the sample well. Then, electrophoresis was initiated with split-flow electrokinetic injection (20) of ssDNA molecules from the sample inlet toward the waste well with an electric field of 200 V/cm for 90 s, while grounding the sample well and floating both the buffer well and buffer waste well.…”
Section: Microchip Electrophoresismentioning
confidence: 99%